Exploratory and inferential multivariate statistical techniques for multidimensional count and binary data with applications in R - Ntushelo, Nombasa Sheroline (Stellenbosch : Stellenbosch University, 2011)
Thesis (MComm)--Stellenbosch University, 2011.